Performance studies, actor training and boutique borrowing - Freeman, John (Intellect, 2013)
Informed by 25 years of lecturing in UK universities and a recent relocation to Australia, this article suggests that the ways in which performance studies has sometimes collapsed into a type of watered-down drama school approach is problematic within the non-vocational areas of the university sector. The drive of the article is that, rather than seeking to emulate the training focus of drama schools, university drama, theatre and performance programmes need to hold fast to traditions of study in ways that fuse innovative pedagogy with shifts in opportunities for graduates. In this way, the illusion of training makes way for learning that makes a positive feature of low staff/student contact hours and places emphasis on creativity rather than theatre craft.